13+6z=7(z-1)

Simple and best practice solution for 13+6z=7(z-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+6z=7(z-1) equation:


Simplifying
13 + 6z = 7(z + -1)

Reorder the terms:
13 + 6z = 7(-1 + z)
13 + 6z = (-1 * 7 + z * 7)
13 + 6z = (-7 + 7z)

Solving
13 + 6z = -7 + 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
13 + 6z + -7z = -7 + 7z + -7z

Combine like terms: 6z + -7z = -1z
13 + -1z = -7 + 7z + -7z

Combine like terms: 7z + -7z = 0
13 + -1z = -7 + 0
13 + -1z = -7

Add '-13' to each side of the equation.
13 + -13 + -1z = -7 + -13

Combine like terms: 13 + -13 = 0
0 + -1z = -7 + -13
-1z = -7 + -13

Combine like terms: -7 + -13 = -20
-1z = -20

Divide each side by '-1'.
z = 20

Simplifying
z = 20

See similar equations:

| 3(4x-9)=29 | | 4x^3+12x^2+16=0 | | 3c+47=9c+41 | | 4(5)+y=24 | | 100y-2x=0 | | 15b=7b+40 | | 3p-1-2x+9=0 | | 19t+31=2t+65 | | r^2=88 | | 6h+8=26 | | 10y-2x=5 | | -1[7x+6(x+1)]=-4x-6 | | 2y-30=3y-54 | | (11x-25)+(24+10)=90 | | 3+10b-5-4b= | | 3y+8=y+66 | | -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 | | 2y=y+50 | | -80=8(7-2x)-(2x-8) | | 11x-4=10x+25 | | 16y-8(3y-2)=-2424 | | 6x+3+87= | | 13y-17+145=180 | | 1.3y-18=2 | | -10+5x=-55 | | 2x=4x-50 | | 2s=s+22 | | 4h-6=7 | | 2t=t+100 | | 3x+7+56= |

Equations solver categories